Examinations of soil waterbalance in different crop-rotation systems of maize - Dóka, Lajos Fülöp (Acta Agraria Debreceniensis, 2009)
We examined the change of the time of water balance of soil in 25 years old experiment, on chernozem soil, in different croprotation systems (mono-, bi- and triculture) in dry (2007) and rainy (2008) cropyear in maizestock. According to our findings the values of waterdeficit of soil of maizestock were much smaller in 2008 than values of last year in not irrigated and irrigated plots of three of crop-rotation systems because of favourable supply of precipitation. We found difference between values of waterdeficit of two irrigation treatments. We measured smaller values in irrigated plots of three of crop-rotation systems before sowing.  Waterstock of soil started to decrease with the rising of average temperature and despite of increasing of precipitation quantity in this way we calculated higher values of waterdeficit. Precipitation in August and high average temperature intensified the waterdeficit. Waterdeficit achieved highest values of croptime to front of September. We examined waterbalance of soilprofile in 0-200 cm and we concluded that the waterdeficit of the 80-120 cm soilzone was most intensiv in not irrigated and irrigated treatments because of significant rootmass.